THE IDEA OF SUBJECTIVITY AND DIALOGUE IN THE EDUCATION OF A DISABLED CHILD - Klajmon-Lech, Urszula (Educological discourse, 2018)
The subject-oriented perception of a learner is a sine qua non of effective education. The idea of subjectivity in education is related to the idea of dialogicality. Taking into account subjectivity and the need for permanent dialogue is an important task of educating a child with disability. The first range of both ideas is associated with the relations which occur between parents (the first and most important educators and guardians of a child) and specialists (doctors of various specializations, physiotherapists and, first of all, teachers who work with disabled children). The second range concerns the relations between parents and a disabled child. What seems interesting is finding the answer to the question whether the idea of subjectivity and dialogicality is fully implemented in both ranges.